2020
DOI: 10.1117/1.ap.2.2.026003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light–matter interactions in dielectric nanostructures via machine-learning approach

Abstract: A key concept underlying the specific functionalities of metasurfaces, i.e. arrays of subwavelength nanoparticles, is the use of constituent components to shape the wavefront of the light, on-demand. Metasurfaces are versatile and novel platforms to manipulate the scattering, colour, phase or the intensity of the light. Currently, one of the typical approaches for designing a metasurface is to optimize one or two variables, among a vast number of fixed parameters, such as various materials' properties and coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 92 publications
0
59
0
Order By: Relevance
“…54 Further optimization could be achieved by employing machine learning approaches to simultaneously enhance light-matter interactions. 55 We believe that by enhancing the SFG conversion efficiency, continuous-wave nonlinear upconversion is achievable. Furthermore, the employment of sensitive CMOS cameras and additional devices such as intensifiers can ease the conversion efficiency requirements.…”
Section: Discussionmentioning
confidence: 98%
“…54 Further optimization could be achieved by employing machine learning approaches to simultaneously enhance light-matter interactions. 55 We believe that by enhancing the SFG conversion efficiency, continuous-wave nonlinear upconversion is achievable. Furthermore, the employment of sensitive CMOS cameras and additional devices such as intensifiers can ease the conversion efficiency requirements.…”
Section: Discussionmentioning
confidence: 98%
“…There should be also special attention to the detector, as this should have low noise amplifiers and probably with heterodyne techniques given that the expected voltage differences are small. We envision in the future using machine learning [33] to solve the inverse problem in scatterometry by building a comprehensive database based on calculations as presented in this paper to analyze the experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…The machine-learning approach is a thriving frontier field that provides an approach to improve the efficiency of research. It has been demonstrated that machine learning could enhance light–matter interactions 343 , providing good insight into plasmonic tweezers design and application research 316 . In addition, nanostructures composed of dielectric resonators can exhibit many of the same features as plasmonics, such as high surface-enhanced spectroscopies with low heat conversion 344 and nonlinear optical response processes 345 , giving rise to superior performance in comparison to their lossy plasmonic counterparts.…”
Section: Prospectsmentioning
confidence: 99%